NMDA and AMPA receptor physiology and role in visceral hypersensitivity: a review. Issue 5 (31st March 2022) - Cheng, Fangli; Du, Lijun; Kim, John J.; Zhu, Feng; He, Huiqin; Dai, Ning
Abstract : N -methyl-d -aspartate receptors (NMDARs) and alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptors (AMPARs) are excitatory neurotransmission receptors of the central nervous system and play vital roles in synaptic plasticity. Although not fully elucidated, visceral hypersensitivity is one of the most well-characterized pathophysiologic abnormalities of functional gastrointestinal diseases and appears to be associated with increased synaptic plasticity. In this study, we review the updated findings on the physiology of NMDARs and AMPARs and their relation to visceral hypersensitivity, which propose directions for future research in this field with evolving importance.